1956
DOI: 10.2307/2145032
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Society: The Relation Between Energy, Social Change, and Economic Development, by Fred Cottrell

Abstract: Business & Economics-484 pages of how the evolution of alternative energy converters has impacted the growth of civilization. Energy And Society The Relation Between Energy, Social Change. Published: 1953 New sources of energy and economic development. Energy and society the relation between energy, social change, and economic Energy availability and energy sources as determinants of societal. At a time when many of the theories about history and society refer. relation between energy, social change, and econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Renewable energy is preferred over nonrenewable because later is dangerous for the environment and people’s health, so renewable energy is desirable. The results generated by the study are similar to outcomes by Barber (1956), Wilkinson et al (1982), Roberts and Grimes (1997), Cottrell (2009), Sathaye et al (2011), Colombo et al (2013), Papanelopoulou and Nieto-Galan (2016), Sen and Ganguly (2017), Gámez et al (2017), Hanif et al (2020), Sial et al (2022) and Wang et al (2022) that increase in renewable energy reduces the global warming, and it promotes positive implications for social development.…”
Section: Methodology and Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Renewable energy is preferred over nonrenewable because later is dangerous for the environment and people’s health, so renewable energy is desirable. The results generated by the study are similar to outcomes by Barber (1956), Wilkinson et al (1982), Roberts and Grimes (1997), Cottrell (2009), Sathaye et al (2011), Colombo et al (2013), Papanelopoulou and Nieto-Galan (2016), Sen and Ganguly (2017), Gámez et al (2017), Hanif et al (2020), Sial et al (2022) and Wang et al (2022) that increase in renewable energy reduces the global warming, and it promotes positive implications for social development.…”
Section: Methodology and Resultssupporting
confidence: 83%
“…They also studied the reverse scenario and concluded that a reduction in 0.5°C warming would increase China's GDP by 0.04%. Barber (1956), in his book Energy and Society: The Relation Between Energy, Social Change, and Economic Development, concluded that think beyond the traditional view of nation development like race, religion, culture, army and geography and accept that available energy is the basic driver of social development. Wilkinson et al (1982) investigated the use of energy and social disruption in western countries and concluded that the results were inconsistent and needed theoretical background and proper methodology.…”
Section: Literature Review 21 Impact Of Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…The research provides a comprehensive understanding of how the political and historical context in Vietnam significantly influences religious conversion. It suggests that shifts in the socio-political landscape, including political upheavals and critical historical events, can catalyze individuals to explore and adopt new religious beliefs (Cottrell, 2009). This finding highlights the dynamic nature of religious affiliation, showing its responsiveness to external societal changes.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 80%
“…However, the motivation for religious conversion is only sometimes driven by economic or material benefits. Seul (1999), Rambo (1993), andCottrell (2009) point out that social pressures and the desire to belong to a particular community can also be significant factors. This aspect emphasizes the human need for social connection and acceptance, which can be fulfilled through religious affiliation.…”
Section: Socio-economic and Motivation Of Religious Conversionmentioning
confidence: 99%